74.8k views
0 votes
I am not understanding this question can you help me solve this? Please I desperately need your help

I am not understanding this question can you help me solve this? Please I desperately-example-1

1 Answer

6 votes

Given:


\[g\left(x\right)=\left\{\begin{matrix}\sqrt[3]{x+5} \\ -{{x}^2}+11\end{matrix}\text{ }\begin{matrix}x\le-4 \\ x>-4\end{matrix}\right.\]

To find:

The value of:


g(-4)

Step-by-step explanation:

For x = -4, we can consider the below function,


g(x)=\sqrt[3]{x+5}

Substituting the value x = -4,


\begin{gathered} g(-4)=\sqrt[3]{-4+5} \\ =\sqrt[3]{1} \\ =1 \end{gathered}

Final answer:

Hence, the required solution is:


(A)\text{ 1}

User Mirco Bellagamba
by
5.1k points